Optimal monetary policy in an operational medium-sized DSGE model - Malin Adolfson; Stefan Laséen; Jesper Lindé; Lars E.O. Svensson (Sveriges Riksbank, 2008)
We show how to construct optimal policy projections in Ramses, the Riksbank's openeconomy medium-sized DSGE model for forecasting and policy analysis. Bayesian estimation of the parameters of the model indicates that they are relatively invariant to alternative policy assumptions and supports that the model may be regarded as structural in a stable low inflation environment. Past policy of the Riksbank until 2007:3 (the end of the sample used) is better explained as following a simple instrument rule than as optimal policy under commitment. We show and discuss the differences between policy projections for the estimated instrument rule and for optimal policy under commitment, under alternative definitions of the output gap, different initial values of the Lagrange multipliers representing policy in a timeless perspective, and different weights in the central-bank loss function.
Keywords: E52; E58; 330; optimal monetary policy; instrument rules; optimal policy projections; openeconomy DSGE models; Geldpolitik; Geldmengensteuerung; Wirtschaftsprognose; Dynamisches Gleichgewicht; Zentralbank; Schweden